Gamificación y el pensamiento crítico en el proceso de enseñanza - aprendizaje de la escuela “Alonso de Mercadillo” de la ciudad de Loja. - Mejía Molina, Diana Yazmín (2022)
Education is a fundamental pillar for social development, it is there where changes for the development of a country are gestated; however, traditional methods predominate in the classroom, content is still addressed and not skills, questions are raised that validate memory, but not reflection or critical thinking, gamification is incorporated into teaching process, but questions are still those of a test that retrieves information. In this context, the main objective of this research was to articulate gamification as a didactic strategy in the teaching-learning process to develop critical thinking in students of the Alonso de Mercadillo school in the city of Loja. The approach used was quantitative, the type of research is descriptive and non- experimental, with a cross-sectional design, the methods used were inductive, analytical- synthetic and statistical, the sample with which we worked is 40 teachers who are part of the institution. The procedures were focused on the bibliographic review; a questionnaire was used for the collection of information that allowed to identify the gamification strategies associated with the development of critical thinking to finally propose methodological guidelines that guide the teacher to gamify in order to develop critical thinking. It is concluded that gamification as a technique presents multiple advantages because it allows to the student to develop critical thinking., skills such as identifying, analyzing, concluding and communicating in active and participatory spaces, hence the need to incorporate it in the teaching-learning process. In addition, gamification in educational processes presents many advantages because it motivates the student to learn through challenges; and it is precisely in this same dynamic where the proposed activities can guide decision-making, autonomy, and reflection on action through metacognition. Key words: Educational games, gamification, critical thinking, teaching-learning process, game articulation.